A comprehensive criterion for slug-annular flow transition based on flow boiling of R134a in microchannels. (June 2019) - Yan, Qiao; Jia, Li; An, Zhoujian; Peng, Qi
Abstract: A microchannel test loop with an air cooling system was established in this study. Experiments were conducted with R134a within 30 parallel rectangular channels of 0.5 mm × 0.5 mm × 45 mm. The heat flux was in the range of 49.9 to 580.1 kW/m 2 and the mass flux was in the range of 132 to 1529 kg/m 2 s in this research, respectively. The saturation temperature in the range of 21.6 to 32.9 °C. The heat transfer coefficient increased with the mass flux and showed a curve like "M"-shape with the increase of heat flux. Under the same conditions of heat and mass flux, the higher saturation temperature was, the lower wall superheat was, and the heat transfer coefficient was improved. The G-x flow patterns map showed that a higher saturation temperature resulted in a lower vapor quality in the channels, which dedicated to the flow patterns distribution in the nuclear boiling region; whereas a lower saturation temperature led to a higher vapor quality, and the convective evaporation dominated. Based on the influences of multiple factors on the slug-annular flow transition in microchannels, a new predicting correlation for the vapor quality at the valley point of the "M"-shape was proposed, which provided a criterion for the transition from nuclear boiling mechanism into convective evaporation mechanism.